A volume‐independent conformity index for stereotactic radiosurgery. Issue 5 (12th April 2022) - Oh, Seungjong; Awan, Musaddiq J.; Monroe, James I.; Liang, Yun; Wegner, Rodney E.; Karlovits, Stephen; Machtay, Mitchell; Lo, Simon S.; Sloan, Andrew; Sohn, Jason W.
Abstract: Purpose: To develop a volume‐independent conformity metric called the Gaussian Weighted Conformity Index (GWCI) to evaluate stereotactic radiosurgery/radiotherapy (SRS/SRT) plans for small brain tumors. Methods: A signed bi‐directional local distance (BLD) between the prescription isodose line and the target contour is determined for each point along the tumor contour (positive distance represents under‐coverage). A similarity score function (SF) is derived from Gaussian function, penalizing under‐ and over‐coverage at each point by assigning standard deviations of the Gaussian function. Each point along the dose line contour is scored with this SF. The average of the similarity scores determines the GWCI. A total of 40 targets from 18 patients who received Gamma‐Knife SRS/SRT treatments were analyzed to determine appropriate penalty criteria. The resulting GWCIs for test cases already deemed clinically acceptable are presented and compared to the same cases scored with the New Conformity Index to determine the influence of tumor volumes on the two conformity indices (CIs). Results: A total of four penalty combinations were tested based on the signed BLDs from the 40 targets. A GWCI of 0.9 is proposed as a cutoff for plan acceptability. The GWCI exhibits no target volume dependency as designed. Conclusion: A limitation of current CIs, volume dependency, becomes apparent when applied to SRS/SRT plans. The GWCI appears to be a more robust index, which penalizes over‐ and under‐coverage of tumors and is not skewed by the tumor volume.